Cultura de paz e educação para a paz: contextos, conflitos e práticas de orientadores educacionais - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The objective of this research is to discuss the contexts, conflicts and practice of the Educational Advisor articulated with the elements of Culture and Education for Peace. For this, the theoretical framework is constructed by Salles Filho (2019), Morin (2005, 2011, 2015, 2021), Jares (2002) and Guimarães (2011). The central concepts are Culture and Education for Peace, School Management and Complexity, such concepts were assumed and thought about an intertwining between the Manifesto 2000, the Pedagogy of Conflictology and the Seven knowledge necessary for the education of the future. Methodologically, it is a qualitative research, built from a semi-structured interview, with nine Educational Advisors, working in the public school system in Bagé-RS. The results were constructed based on Discursive Textual Analysis (Moraes; Galiazzi, 2016) and organized into three categories: Contexts, Conflicts and Professional Practice of Educational Counselors in the light of the Culture of Peace, School Management and Seven Knowledge. These categories allow us to perceive, for example, the presence of virtualities and negligence, as a source of conflict, which, combined with the lack of tolerance and dialogue, affect coexistence. They also point out the partnership between school and family and the importance of training management professionals in the face of adversities and diversities present in the educational environment. It is important to encourage the school community to understand the contexts and take non-violent conflict actions.
Keywords: Cultura da paz; Educação para paz; Gestão escolar; Culture of peace; Education for peace; School management; CNPQ::CIENCIAS HUMANAS